Effect of Leaflet-Based Education on Pregnant Women’s Knowledge About Stunting - Arika Savitri; Jamhariyah Jamhariyah; Susilawati Susilawati (Minsight: Midwifery Insight and Innovation Journal, 2026)
Knowledge of pregnant women is one of the internal factors that influences the increase in stunting. This is due to the lack of knowledge of pregnant women regarding the impact of stunting.  the prevalence of stunting is 6.35% (9,837 stunted toddlers) out of 154,824 toddlers. In the Arjasa health center 12.26% (333 stunted toddlers) out of 2,716 toddlers, while in Arjasa Village 13.7% (97 stunted toddlers) out of 705 toddlers. Based on preliminary studies, 6 out of 10 pregnant women could not answer about stunting. Maternal knowledge is one of the elements that can influence stunting rates. The purpose is to examine the difference in stunting knowledge before and after receiving education by leaflet media. A one-group pretest-posttest design was used in this pre-experimental study. The population consisted of 67 pregnant women, with a sample of 57 pregnant women drawn using a simple random sampling. The instrument used a questionnaire, analyzed using the Spearman Test. Pregnant mothers have good knowledge of stunting before receiving an education (10.5%) and after receiving education (86%). The Spearman test resulted in a p-value of 0.000, which is less than the threshold of α (0.05). The null hypothesis was rejected, indicating a significant difference. There is a difference in pregnant women's knowledge of stunting after receiving education through leaflet media. This has resulted in increased awareness of stunting among pregnant women, and it is hoped that leaflet media will become a viable medium for giving health education to pregnant women